2022
DOI: 10.3389/fpubh.2022.882361
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Neighborhood-Built Environment and Elderly Health: A Research Based on Heterogeneity of Age and Gender Groups in Beijing

Abstract: BackgroundThe built environment quality of neighborhoods has a significant impact on the health of the elderly. Although there has been a wealth of studies on low-density Western cities, research on the impacts of built environment on elderly health in high-density Chinese cities is far from sufficient. The pathways by which the built environment affects elderly health remain to be observed, particularly whether such pathways vary for different ages and genders.MethodsBased on the data of the “Fourth Survey on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…We also collected information from some participants regarding how long (about 5–10 minutes) and how far (approximately 500 m) they were willing to walk to reach facilities and services in the study area. Additionally, previous studies have reported that neighborhood built environments can be effectively captured using a 500 m radius buffer based on the participants’ residential locations [ 5 , 75 , 76 ]). The 500 m radius buffer around each participant’s residential location was used to delineate contextual areas for extracting and measuring the built environment variables.…”
Section: Methods and Datamentioning
confidence: 99%
“…We also collected information from some participants regarding how long (about 5–10 minutes) and how far (approximately 500 m) they were willing to walk to reach facilities and services in the study area. Additionally, previous studies have reported that neighborhood built environments can be effectively captured using a 500 m radius buffer based on the participants’ residential locations [ 5 , 75 , 76 ]). The 500 m radius buffer around each participant’s residential location was used to delineate contextual areas for extracting and measuring the built environment variables.…”
Section: Methods and Datamentioning
confidence: 99%
“…Similar to compact city literature, we also use population density , land use mix , street connectivity , and transit accessibility as our compactness measures (Ewing et al, 2014; Fan et al, 2019; Tsai, 2005). Studies of aging in mainland China and Hong Kong have found various components of compactness such as street connectivity (Wu et al, 2019), mixed land use, shorter distance to transit and neighborhood services (Chen et al, 2022; Lang et al, 2019; Li et al, 2022; Liu et al, 2021; Guo et al 2021) are important factors for the health of older adults. Table 2 summarizes our calculations of each indicator of the urban compact index (UCI), and we explain it below.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Liu et al (2019), using China’s 2005 census, found that counties having higher population density are associated with higher older adults SRH, although the study includes both rural and urban counties, so the positive effects of density may be attributed to a higher standard of living in cities rather than compactness, and the 2005 data are dated. Research on individual cities using ethnographical or quantitative analysis methods in Beijing (Dong and Qin, 2017; Li et al, 2022; Yu and Rosenberg, 2020) and Nanjing (Wu et al, 2019) all suggests that compact built environments promote positive physical activities, social interactions, access to daily service, and emotional belonging. Studies in Hong Kong have been particularly prolific and reveal the nonlinear relationships between the physical and mental health of older adults, and the urban compactness measured by population density, street connectivity, and land use diversity (Chen et al, 2022; Guo et al, 2021; Lang et al, 2019; Liu et al, 2021; Lu et al, 2017).…”
Section: Declining Compactness and Healthy Aging Of Older Adultsmentioning
confidence: 99%
“…Secondly, little has been done to distinguish the heterogeneity of human activities by age in these studies. According to related research ( 43 , 44 ), there are differences in the activity ability, activity scope, and activity purpose of different age groups. For example, the main activity spaces of teenagers are schools and home, the main activity spaces of youth are mainly home and employment places, while the main activity spaces of older adults are mostly home and community parks.…”
Section: Literature Reviewmentioning
confidence: 99%